The Analitical Solution of Linear and Non-Linear Differential- Algebraic Equations (DAEs) with Laplace-Padé Series Method - Nooriza Myrzabekova; Ercan Celık (MANAS: Journal of Engineering)
In this paper, we apply Laplace-Padé Series method to solve linear and non-linear differentialalgebraicequations (DAEs). Firstly, The basic properties of the Laplace-Padé Series method aregiven. Secondly, we calculate the arbitrary order power series of differential-algebraic equations(DAEs), then convert it to the series form Laplace-Padé. Then, the three differential-algebraicequations (DAEs) are solved by Laplace-Padé Series method. It was seen that the method gaveeffective and fast results. Therefore, the method can be easily applied to linear and non-lineardifferential-algebraic equations (DAEs) problems in different fields.